AIR POLLUTION ASSESSMENT OF BOKO HARAM AFFECTED LOCAL GOVERNMENT AREAS OF ADAMAWA STATE, NORTH EASTERN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
This study is aimed at assessing the ambient air quality of Local Government Areas affected by Boko Haram insurgency. The study was conducted in both the rainy and dry seasons. Gasman portable gas monitor was used for the monitoring of CO, NO2, SO2, H2S, and Cl2. CO and H2S were found to be within acceptable limits set by FEPA (10.00 ppm and 8.00 ppm) respectively in both seasons in all locations except Hong LGA, where CO was 11.11 ppm. NO2, SO2 and Cl2 were all above acceptable limits of 0.06 ppm, 0.1 ppm and 0.01 ppm respectively. The Air Pollution Index rating indicated that all the locationswere severely contaminated, except for Michika, Madagali and the control locations which were below 100 in the rainy season. The rainy season concentrations of these pollutants are lower than the dry season due to dissolution of the pollutants by the rains. The result of the pollution level is very poor and is a threat to the health of the populace. Thus this research recommends appropriate measures to be taken to enhance a safe environment for the people in these locations for healthy human living
Keywords: Adamawa State, Ambient air Pollution, Boko Haram, Contamination, Index, Pollution, and Rainy and dry seasons